PEMBELAJARAN DARING, STRES DAN ZOOM FATIGUE PADA MAHASISWA D-III KEPERAWATAN SELAMA PANDEMI COVID-19 - Purba, Sri Dearmaita; Sijabat, Flora; Amila, Amila (Indonesian Trust Health Journal, 2022)
The Covid-19 pandemic that occurred in Indonesia led to the implementation of online or online learning in educational institutions so that the teaching and learning process can be carried out. In practice, online learning in universities has positive and negative impacts, especially in the health sector. The purpose of the study was to determine the effect of online learning on stress and zoom fatigue as well as the characteristics that affect D III nursing students at Sari Mutiara University, Indonesia. This research is a correlation analytic study with a cross sectional design. The sampling technique used purposive sampling with the number of respondents as many as 44 people. Data collection was carried out by distributing questionnaires through Google Forms which were sent to students by researchers via whatsapp. The bivariate test used to determine the relationship between online learning and the characteristics that affect stress and zoom fatigue is the Spearman correlation test. The results showed that there was a relationship between online learning and stress levels (p value = 0.009 ; r = 0.389). There is no relationship between age (p value = 0.327 ; r = -0.151); gender (p value = 0.851, r = 0.029); internet connection (p value = 0.276 ; r = -0.098); duration of online learning (p value = 0.369; r = -0.139) with the stress level of nursing students. There is a relationship between online learning (p value = 0.049; r = 0.299, age (p value = 0.018; r = 0.355), duration of online learning (p value = 0.037; r = 0.316) with zoom fatigue in nursing students. There is no relationship between gender (p value = 0.527, r = 0.098), internet connection (p value = 0.929; r = 0.014) and zoom fatigue in nursing students. Lecturers need to innovate/modify learning media with various applications that do not require high concentration, so that fatigue and stress on students do not occur. Abstrak Pandemi Covid-19 yang terjadi di Indonesia menyebabkan diterapkannya pembelajaran daring atau online diinstitusi pendidikan supaya proses belajar mengajar dapat dilaksanakan. Dalam pelaksanaannya pembelajaran daring di perguruan tinggi memiliki dampak positif dan negatif terutama dibidang kesehatan. Tujuan penelitian adalah untuk mengetahui pengaruh pembelajaran online terhadap stres dan zoom fatigue serta karakteristik yang mempengaruhi pada mahasiswa D-III keperawatan Universitas Sari Mutiara Indonesia. Penelitian ini merupakan penelitian analitik korelasi dengan rancangan cross sectional. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah responden sebanyak 44 orang. Pengumpulan data dilakukan dengan penyebaran angket melalui Google Form yang dikirim kepada mahasiswa oleh peneliti melalui whatsapp. Uji bivariat yang digunakan untuk mengetahui hubungan pembelajaran online dan karakteristik yang mempengaruhi stres dan zoom fatigue adalah uji korelasi Spearman. Hasil penelitian menunjukkan ada hubungan antara pembelajaran daring dengan tingkat stres (p value = 0,009 ; r = 0,389). Tidak ada hubungan antara usia (p value = 0,327 ; r = -0,151); jenis kelamin (p value = 0,851, r = 0,029); koneksi internet (p value = 0,276 ; r = -0,098); durasi belajar daring (p value = 0,369; r = -0,139) dengan tingkat stres mahasiswa keperawatan. Ada hubungan antara pembelajaran daring (p value = 0,049 ; r = 0,299, usia (p value = 0,018 ; r = 0,355), durasi belajar daring (p value = 0,037; r = 0,316) dengan zoom fatigue pada mahasiswa keperawatan. Tidak ada hubungan antara jenis kelamin (p value = 0,527, r = 0,098), koneksi internet (p value = 0,929 ; r = 0,014) dengan zoom fatigue pada mahasiswa keperawatan. Dosen perlu melakukan inovasi/modifikasi media pembelajaran dengan berbagai aplikasi yang tidak memerlukan konsentrasi yang tinggi, sehingga kelelahan dan stress pada mahasiswa tidak terjadi.